Management of systemic AL amyloidosis: recommendations of the Myeloma Foundation of Australia Medical and Scientific Advisory Group. Issue 4 (April 2015) - Weber, N.; Mollee, P.; Augustson, B.; Brown, R.; Catley, L.; Gibson, J.; Harrison, S.; Ho, P. J.; Horvath, N.; Jaksic, W.; Joshua, D.; Quach, H.; et al.
Abstract Systemic AL amyloidosis is a plasma cell dyscrasia with a characteristic clinical phenotype caused by multi‐organ deposition of an amyloidogenic monoclonal protein. This condition poses a unique management challenge due to the complexity of the clinical presentation and the narrow therapeutic window of available therapies. Improved appreciation of the need for risk stratification, standardised use of sensitive laboratory testing for monitoring disease response, vigilant supportive care and the availability of newer agents with more favourable toxicity profiles have contributed to the improvement in treatment‐related mortality and overall survival seen over the past decade. Nonetheless, with respect to the optimal management approach, there is a paucity of high‐level clinical evidence due to the rarity of the disease, and enrolment in clinical trials is still the preferred approach where available. This review will summarise the Clinical Practice Guidelines on the Management of Systemic Light Chain (AL) Amyloidosis recently prepared by the Medical Scientific Advisory Group of the Myeloma Foundation of Australia. It is hoped that these guidelines will assist clinicians in better understanding and optimising the management of this difficult disease.